2015
DOI: 10.1002/ajmg.a.37429
|View full text |Cite
|
Sign up to set email alerts
|

Discordant clinical phenotype in monozygotic twins with Alagille syndrome: Possible influence of non‐genetic factors

Abstract: Alagille syndrome is a multisystem developmental disorder characterized by bile duct paucity, congenital heart disease, vertebral anomalies, posterior embryotoxon, and characteristic facial features. Alagille syndrome is typically the result of germline mutations in JAG1 or NOTCH2 and is one of several human diseases caused by Notch signaling abnormalities. A wide phenotypic spectrum has been well documented in Alagille syndrome. Therefore, monozygotic twins with Alagille syndrome provide a unique opportunity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 19 publications
(20 reference statements)
0
13
0
Order By: Relevance
“…This observation suggests that when considering potential genetic modifiers of Notch signaling in Alagille syndrome and perhaps in other diseases of haploinsufficiency, one cannot limit the search to those genes which already have a significant phenotype in a wild-type context. Finally, given the reports on discordant phenotypes in monozygotic twins with ALGS [57,58], environmental factors are likely to contribute to the phenotypic variability in this disease, as was shown in an elegant study of gene-environment interaction in another Notch-related disease, namely congenital scoliosis [119].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation suggests that when considering potential genetic modifiers of Notch signaling in Alagille syndrome and perhaps in other diseases of haploinsufficiency, one cannot limit the search to those genes which already have a significant phenotype in a wild-type context. Finally, given the reports on discordant phenotypes in monozygotic twins with ALGS [57,58], environmental factors are likely to contribute to the phenotypic variability in this disease, as was shown in an elegant study of gene-environment interaction in another Notch-related disease, namely congenital scoliosis [119].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no known genotype-phenotype correlation in ALGS [53,54,55,56]. Importantly, several studies have reported discordant phenotypes in monozygotic twins with ALGS [57,58,59], strongly suggesting a key role for the environment in determining the severity of the ALGS phenotypes. In addition, Jag1 heterozygous phenotypes in mice are highly sensitive to genetic background and to the gene dosage of other Notch pathway components [9,10,60,61,62], suggesting that genetic modifiers are also likely to contribute to the ALGS phenotypic variability.…”
Section: The Role Of Notch Signaling and Its Modifiers In The Pathmentioning
confidence: 99%
“…Some of the patients in our cohort have been previously reported and are included here to provide a comprehensive summary of our clinical study, with prior reports referenced in all corresponding tables (Bauer et al, ; Colliton et al, ; Heritage et al, ; Izumi et al, ; Kamath et al, ; Kamath et al, ; Kamath et al, ; Krantz et al, ; Laufer‐Cahana et al, ; Li et al, ; Lin et al, ; McDaniell et al, ; Morrissette, Colliton, & Spinner, ; Oda et al, ; Warthen et al, ). Our cohort contains both probands and affected family members.…”
Section: Methodsmentioning
confidence: 99%
“…Early studies aimed to determine whether the location of pathogenic variants is able to predict the clinical manifestation of the disease do not support a genotype‐phenotype correlation (Crosnier et al, ; Spinner et al, ). Conversely, a high degree of variable expressivity has been observed, and often significant phenotypic variability is reported in families harboring the same pathogenic variant (Dhorne‐Pollet, Deleuze, Hadchouel, & Bonaiti‐Pellie, ; Elmslie et al, ; Emerick et al, ; Izumi et al, ; Kamath, Bason, Piccoli, Krantz, & Spinner, ; Kamath, Krantz, Spinner, Heubi, & Piccoli, ; Krantz et al, ; Shulman, Hyams, Gunta, Greenstein, & Cassidy, ). These observations have led to the hypothesis that a second gene could act as a modifier, and studies have been carried out to test this theory.…”
Section: Introductionmentioning
confidence: 99%
“…Alagille syndrome is a condition consisting of CHD, hepatic complications including bile duct paucity and cholestasis, and skeletal and ophthalmologic anomalies. There is significant variability in the expression even within the same family, with some individuals displaying very mild features and others with severe CHD or liver disease leading to transplant or death (Quiros-Tejeira et al 1999;Kamath et al 2003;Izumi et al 2016;Ziesenitz et al 2016). More than 90% of patients with Alagille syndrome have cardiovascular involvement.…”
Section: Alagille Syndromementioning
confidence: 99%